Study English IELTS Preparation - Shymkiw, Anna (Nxb. Trẻ, 2011)
Study English - IELTS Preparation is a unique English language resource developed by ABC Pacifc and INSEARCH UTS. This is the first time audio-visual materials using authentic spoken English have been used to develop and teach English language skills with particular reference and application to IELTS preparation.